HIV/AIDS and Nutrition: A Review of Current Evidence - KC, Tulza (Journal of Nursing Education of Nepal, 2023)
Human Immune Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) epidemic is increasingly driven by and contributes to factors that also create malnutrition. Nutrition plays a critical role in comprehensive care, support and treatment of HIV infected people. There are complex interactions between nutrition and HIV/AIDS. HIV progressively weakens the immune system and leads to malnutrition. Malnutrition worsens the effects of HIV and contributes to more rapid progression to AIDS. The association of malnutrition, micronutrient deficiencies, weight loss and muscle wasting with the increased morbidity and mortality is clearly present in patients living with HIV/ AIDS. The available evidence shows that nutritional education, counseling and supplementation improve nutritional status among people with HIV/AIDS. Thus to conclude, nutrition should be fully incorporated into care, support and treatment for HIV-infected people and affected families.